PENGARUH INVESTASI, PENGELUARAN PEMERINTAH DAN TENAGA KERJA TERHADAP PDRB PROVINSI BANTEN - Mamai Maisaroh; Havid Risyanto (EkBis: Jurnal Ekonomi dan Bisnis, 2017)
The research based on economic growth neo clasic model which develop by Abramovits and Solow, they say the economic growth (in area measurment by growth of gross regional domestic product). Its depent on production factors such as capital, labor and tecnology. Althought capital based on investment and goverment expediture. While labor  based on labor force work. The research focus is how investment, goverment expediture and labor according simultant and partial to gross regional domestic product of district in Banten Province. The aims of teh research in to knowing the influence of invesment, goverment expenditure and labor togross regional domestic product of district in Banten Province 2010-2015 period. The method used in this research is regression analysis of panel data and supporting sofware from eviews 9. The research study concluded invesment, goverment expenditure and labor with simultant and partial was positive and significant impact on the gross regional domestic product of district in Banten Province, so in an effort to increase GDP it is necessary that the role of local government through government policies and expenditures is expected to stimulate increased investment and employment generation in order to achieve economic growth and increase in income per capita society. Key Word : Invesment, Goverment Expenditure, Labor, GDP